Barriers to Cross-border eCommerce in the EU Digital Single Market - Néstor Duch-Brown; Bertin Martens (European Commission, Joint Research Centre (JRC), 2015)
This report presents empirical evidence about the internationalisation of European online firms. After describing some characteristics that define the internationalisation of firms engaged in online activities, it mainly focuses on the obstacles that these firms face when trying to sell their products and/or services to other EU Member States. It relies on data from a firm survey carried out in January-February 2015 in four different sectors (manufacturing, wholesale and retail, accommodation and food and information and communication) and is complemented with additional sources of information. We find that a limited number of barriers really matter for online trade. These include settling the costs of cross-border disputes, suppliers' restrictions to selling cross-border, delivery costs, taxation rules, and knowledge of the rules abroad. In line with the offline trade literature, the data confirm that they matter mostly for small firms, which find it harder to overcome the fixed trade costs associated with these barriers.
Keywords: D22; 330; digital single market; e-commerce; cross-border online trade; online firms